Lung Function and Chronic Exposure to Air pollution A Study on adolescent male of urban area. (Journal of Dhaka National Medical College & Hospital, 2013)
Background Chronic exposure to heavily polluted air affects the respiratory status. Objectives: To observe the effects of air pollution on pulmonary functions of adolescent male living in urban areas of Bangladesh. Methods: This cross-sectional study was done in the department of Physiology, BSMMU. For this purpose, 60 apparently healthy adolescent male of age 13 to 18 were selected from different slum areas of Dhaka city. Sex and age matched 55 subjects were taken as control from rural area of Bangladesh. All subjects were of low socio-economic status and living in the corresponding areas since birth. In the study, Forced vital capacity (FVC), Forced expiratory volume in first second (FEV1), FEV1 /FVC % and Peak expiratory flow rate (PEFR) were estimated by VMI ventilometer on standing position. Statistical analysis was done by using Z test. Result: The mean measured values of FVC, FEV1, FEV1/ FVC% and PEFR were lower in the experimental group than in the control group. FVC and FEV1 were lowered significantly (p